Do Prudential Regulations Influence Banks’ Tax Burden? Evidence from Indonesia - Renaldy Wira Pratama; Subagio Efendi (Directorate General of Taxes, 2025)
This study examines the effect of existing prudential regulations on banks’ income tax burden, addressing an existing gap in prior literature that has rarely linked regulatory compliance with fiscal outcomes. We focus on two main prudential elements in Indonesia: the minimum capital adequacy ratio provision, which mandates a capital buffer of at least eight per cent of risk-weighted assets, and the maximum non-performing loan ceiling, which limits bad debts to less than five per cent of total disbursed loans. Using panel data of 47 banks listed on the Indonesia Stock Exchange from 2012 to 2022 and applying multiple regression estimations, this study offers novel evidence on the regulatory-tax nexus. The results show that the minimum capital buffer provision does not influence banks’ effective tax rates, whereas the maximum bad-debt ceiling has a substantial influence. Specifically, a one-percentage-point increase in the non-performing loan ratio is associated with a 0.6 to 0.8 percentage-point increase in the tax burden, reflecting the stringent requirements of tax-deductibility of bad debt. These findings highlight the critical role of prudential supervision in shaping fiscal responsibilities, as suggested by previous studies. More broadly, this study contributes to the banking and tax literature by demonstrating how financial stability regulations can influence fiscal accountability, with lessons relevant to both emerging economies and global tax practices.